Auditoría informática en las áreas de almacén y activaciones de la empresa Centracom S.A. (2013)
The general objective of this audit was to evaluate the processes done in the information systems at the storage areas and activations of the company Centracom S.A. considering that these two areas are the most vulnerable ones, as a result of submitting false information, incorrect documents and past due inventories among others, can be lead to the course of operations and generated drawbacks that can be represented in fines for company. Thus, because of the evidence found they make a report which contains both checks and the next step as possible solutions to the present problem.